COFFEE SHOP AND THE CONSUMER BEHAVIOR OF TEENAGERS: A CRITICAL STUDY WITHIN THE FRAMEWORK OF THE SHARIA ECONOMY - Saifuddin; Riskiya Dwi Novem Wulandari; Moh Khoirul Anam (Universitas Muhammadiyah Surabaya, 2024)
This research aims to understand the characteristics and patterns of adolescent consumer behavior related to their participation in coffee shop culture and to determine the impact of adolescent consumer behavior on coffee culture from the perspective of Islamic Economics. The phenomenon of the increasing popularity of coffee shops among teenagers indicates a change in consumption patterns, which has the potential to lead to consumerist behavior. Consumerist behavior is considered excessive and inconsistent with the principles of justice and balance in wealth management. This research uses a qualitative method with a case study approach. The data sources consist of primary and secondary data. Data were obtained through in-depth interviews with teenage visitors to Cafe Rooster, observations, and documentation. The results of this study show that: 1) Coffee shops have become a symbol of social status and a popular gathering place among teenagers, driven by peer pressure and the desire for acceptance. Teenagers are driven to spend money at coffee shops to express themselves, seek enjoyment, and follow trends promoted through social media platforms like Instagram, Facebook, and Twitter, which also influence their purchasing decisions. 2) From the perspective of Islamic economics, the consumer behavior of teenagers in coffee shop culture has negative impacts, such as uncontrolled spending and being contrary to the principle of prudence in Islam, which is opposed to the value of blessings in Islam and has the potential to cause financial problems in the future. Therefore, a balance between consumption and saving needs to be maintained.